Rochester Rehabilitation Center : a nonprofit contemplates the purchase of a greeting card company - Oster, Sharon M., (SAGE knowledge. Cases., 2016)
In 2001, George Gieselman, president of the Rochester Rehabilitation Center, was considering a unique proposition for his nonprofit organization. A Rochester-based greeting card company, Parrett Paper, had fallen on hard times and was looking for a buyer. The Center already operated a division, The Out-Source, which provided direct employment for the disabled individuals who were the clients of the Center. If The Out-Source purchased the card company, the business could potentially generate additional jobs for the disabled as well as provide a source of income. However, the greeting card business seemed to be unlike the other contract work provided by The Out-Source division and therefore might strain the managerial resources of the organization.